2017
DOI: 10.1007/s10928-017-9554-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tenofovir plasma and tissue exposure using a population pharmacokinetic model and bootstrap: a simulation study from observed data

Abstract: Sparse tissue sampling with intensive plasma sampling creates a unique data analysis problem in determining drug exposure in clinically relevant tissues. Tissue exposure may govern drug efficacy, as many drugs exert their actions in tissues. We compared tissue area-under-the-curve (AUC) generated from bootstrapped noncompartmental analysis (NCA) methods and compartmental nonlinear mixed effect (NLME) modeling. A model of observed data after single-dose tenofovir disoproxil fumarate was used to simulate plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several population pharmacokinetic models for tenofovir have been reported previously, the majority when dosed as TDF. [17][18][19][20][21][22][23] An exception is the model by Greene et al, 24 in which the authors describe tenofovir pharmacokinetics after both TDF and TAF administration in men living with HIV in the United States. However, they use two separate models, one when TDF is administered and another when TAF is administered.…”
Section: Discussionmentioning
confidence: 99%
“…Several population pharmacokinetic models for tenofovir have been reported previously, the majority when dosed as TDF. [17][18][19][20][21][22][23] An exception is the model by Greene et al, 24 in which the authors describe tenofovir pharmacokinetics after both TDF and TAF administration in men living with HIV in the United States. However, they use two separate models, one when TDF is administered and another when TAF is administered.…”
Section: Discussionmentioning
confidence: 99%
“…to the complexity of the non-parametric algorithms that are common in machine-learning methods, it is impossible for a human to analyze each tree and execute an explanation of how the machine-learning method works [1,[62][63][64][65]. Thus, using SHAP allows for a similar covariate interpretation as linear regression even if the exact effect-sizes of the covariates cannot be interpreted the way it can in linear regression [15,22,49,[66][67][68]…”
Section: Plos Onementioning
confidence: 99%
“…(Centers for Disease Control and Prevention, 2018) Collins et al recently published a population PK model relating plasma and rectal tissue concentrations of TFV, demonstrating that non-linear mixed-effects (NLME) modeling is a viable approach for predicting TFV tissue exposures using a sparse tissue and rich plasma sampling scheme. (Collins et al, 2017) A diagram of the compartmental model used by Collins et al can be found in Supplementary Figure 2.…”
Section: Tenofovir Disoproxilmentioning
confidence: 99%